The Effectiveness of Health Education on Students’ Knowledge and Attitudes toward Hyperthyroidism at Darul Inayah Islamic Boarding School - Puspitasari, Intan Dwi (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2025)
Hyperthyroidism is one of the endocrine health problems whose prevalence tends to increase in various countries, including Indonesia. Hyperthyroidism is characterized by an increase in thyroid hormones in the body that can cause metabolic, cardiovascular, and emotional and cognitive disorders. In Islamic boarding schools, this issue often goes unnoticed due to the lack of access to health information and low awareness of hyperthyroid symptoms and effects. This condition increases the risk of delayed diagnosis and treatment. Therefore, a promotive and preventive approach through health counseling is one of the effective strategies to increase students’ understanding of this disease. This study aims to determine the effectiveness of health counseling on increasing students’ knowledge and attitudes about hyperthyroidism at Darul Inayah Islamic Boarding School. The study used a quasi-experimental design with a one-group pretest–posttest approach. A total of 40 students aged 15–18 years. Counseling was conducted using visual media and interactive lecture methods. The results showed a significant increase in the knowledge and attitude scores of students after counseling. This finding suggests that health counselling can serve as an effective educational intervention to improve health literacy among adolescents in pesantren settings.